Optimasi Konsentrasi Amylum Sagu (Metroxylon rumphii) sebagai Co-Processed pada Pembuatan Tablet Teofilin - Nor Laili; Annisa' Meyndra Komala; Hidayaturrizqika Maulida; Suprapto Suprapto (Universitas Muhammadiyah Surakarta, 2017)
Tablet preparations are widely used many people for treatment, so the level of production of tablet preparations is quite large and always develops in its formulation. Excipients are generally used in the form of 95% imported materials which are relatively expensive so that production costs will affect the price of tablet preparations which will be more expensive. Based on these considerations, this study uses Indonesian natural excipient with a relatively low cost in the form of sago amylum. This study combines sago amylum and Avicel pH 101 with 5 concentration variations, 90%: 10% (formula 1), 80%: 20% (formula 2), 70%: 30% (formula 3), 60%: 40% (formula 4), and 50%: 50% (formula 5) which produces a co-processed excipient. This co-processed was applied in the manufacture of the Theophylline tablet as a filler, binder and shredder with the direct compression method and tested based on parameters in the Indonesian Pharmacopoeia V. Data analysis using Design Expert® version 11 software to obtain the optimum formula. The co-processed characterization produced has optimum flow properties which are 11.11 g / sec, compressibility = 3.0%, and the stationary angle = 32.0 ° and evaluation of tablet quality uniformity CV = 10.3, hardness x̅ = 6 , 2 kg, fragility = 1.8%, and 46.2 seconds destroyed time. Based on the analysis by Simplex Lattice Design method, it is proved that the more amylum sago concentration increases friability and decreases hardness, while more of Avicel pH 101 decreases friability and increases hardness. It is concluded with the Design Expert software analysis, the optimum co-processed formula was obtained in the form of a combination of 50% sago amylum; 18,18% pasta amylum sago and 31.82% Avicel pH 101.